Lactobacilli producing bispecific llama-derived anti-rotavirus proteins in vivo for rotavirus-induced diarrhea. (May 2011) - Pant, Neha; Marcotte, Harold; Hermans, Pim; Bezemer, Sandra; Frenken, Leon; Johansen, Kari; Hammarströöm, Lennart
Aims: Using genetically engineered lactobacilli, producing high avidity llama VHH domains (referred to as anti-rotavirus proteins; ARPs), to test the effect of multimeric antibody fragments as prophylaxis and therapy against rotavirus infection.Methods: Two ARPs, ARP1 and ARP3, shown to bind to different epitopes and act synergistically against rotavirus, were displayed on the surface of Lactobacillus paracasei as monovalent or bivalent proteins (mono- or bi-specific).Results: Although a nonsignificant difference was observed between lactobacilli producing bispecific ARP3––ARP1 and monomeric ARPs, lactobacilli producing bispecific ARP3––ARP1 were superior at reducing the rate of diarrhea when used for prophylactic and therapeutic intervention in a mouse model of rotavirus infection in comparison to nontreated animals.Conclusion: Expression of bispecific antibodies in lactobacilli resulted in slight improvement of their efficacy. Furthermore, increasing the specificity would theoretically reduce the rate of appearance of viral escape mutants and would have a broader capacity to be effective against a range of viral serotypes.